Pengaruh Pengetahuan Sistem Informasi Akuntansi Dan Tingkat Pendidikan Terhadap Keberhasilan Usaha Mikro Kecil Dan Menengah Di Kota Batam - Elsa Mailani Damanik; Erni Yanti Natalia (Prosiding, 2023)
The purpose of this study is to ascertain how the level of education and SIA knowledge affect the success of MSMEs. The sample for this study consists of MSME actors working in the food and beverage industry. One interpretation of quantitative research techniques is that they are positivism-based research techniques. The results of the hypothesis test were t count 2.100 > t table 1.660 and Sig 0.001. <0.05, so it can be concluded that the AIS Knowledge variable has a significant influence on business success. The education level variable obtained a t count value of 5.742 > Sig 0 point 000 > 0 point 05 and t table 1 point 660. Therefore, it can be said that a major factor affecting business success is the level of education. In light of this, it can be said that Ho is rejected and Ha is accepted, or, to put it another way, that the independent variables simultaneously have a significant impact on the dependent variable.